Выравнивание графика электропотребления в энергосистеме путем использования теплоаккумуляторов - Савицкий, Сергей Михайлович (НТУ "ХПИ", 2016)
В данной статье обсуждается использование комбинированной системы производства тепловой энергии автоматизированными узлами электронагрева (потребителями-регуляторами). Предложено внедрение автоматизированных систем управления электрической нагрузкой в системах электро и теплоснабжения административных зданий. Использование систем аккумуляционного электронагрева, которыми являются потребители-регуляторы, позволяет обеспечить выравнивание графика энергетической нагрузки в системе электроснабжения административных зданий. Проведенная оценка общего эффекта от выравнивания графика электрической нагрузки энергосистемы дает ответ об экономической целесообразности внедрения комбинированных систем теплоснабжения.

This article discusses the use of combined heat power generation system by the automated electric heating units (customers, regulators) and the results of research. The main aim of this study is a feasibility study for the introduction of the automated control systems of electric load in electrical and heating systems of administrative buildings. The use of electrical accumulative heating systems, which are the consumers - regulators, enables alignment of the energy load curve in the power supply system for administrative buildings. In this article, we defined the technical and economic effect of the introduction of energy-efficient combined heat supply system with the accumulation of heat and three-band metering based on the automated transformer type unit for electric heating. Presented power supply system with built-in automated electric load control units can improve the energy efficiency of modes of distribution networks of power supply systems of administrative buildings. The evaluation of the overall effect of the alignment of the electric power system load curve gives an answer about the economic feasibility of the introduction of combined heating systems. The research results can be used in the design and development of electrical and heating systems of administrative buildings to control the selected load.
Alignment graphics power consumption in the power system by the use of heat storage
Keywords: потребитель-регулятор; график электрической нагрузки; энергоэффективность; стоимость электроэнергии; система электроснабжения; consumer-regulator; energy efficiency; power supply system